The Development of a Performance Anxiety Scale for Theatre Actor - Dhani, Kurnia Rahmad (Institut Seni Indonesia Yogyakarta, 2023)
Anxiety is the main barrier for an actor to give a perfect performance that determines the show’s overall quality. However, there have been no studies examining performance anxiety in theatre actors, especially in Indonesia. This study aims to develop a psychological scale that measures the actor’s performance anxiety level. The following five steps are carried out: (a) preparing the items based on the performance-only type of social anxiety; (b) checking content validity using Aiken's V method; (c) conducting a trial scale; (d) testing reliability using Cronbach's alpha; and (e) selecting items. One hundred sixty-three (163) theatre actors were given the Performance Anxiety Scale for Theatre Actors, which consists of 44 items. The analysis showed that Cronbach's alpha coefficient was 0.953 out of 38 passed items (r ≥ 0.30). Thus, the developed Performance Anxiety Scale for Theatre Actors has a good validity and reliability score and can be used properly.